Nisbah Jenis Kelamin Hasil Penetasan Telur Itik Cihateup dan Alabio - Kholid, M.; Rukmiasih, Rukmiasih; Afnan, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Duck eggs are more difficult to hatch than chicken eggs as the duck does not incubate their eggs and the duck eggs need more time to hatch (in 28 days). This study aimed to determine the sex ratio of DOD (Day Old Duck) from two different breeds, namely cihateup from Tasikmalaya West Java and alabio from South Kalimantan. This experiment was conducted from May 2012 to July 2012 at the Hatchery Laboratory of Animal Science Faculty of IPB. 500 eggs consist of 300 alabio eggs and 200 cihateup eggs were used in this experiment. Temperature, humidity, egg weight, egg shape index, hatching weight and mortality were measured. The data of egg weight, egg shape index, and hatching weight were analyzed using t-test, the data of sex ratio DOD were analyzed using chi-square test. The result showed that there were no significant difference between egg weight and egg shape index on sex ratio. Sex ratio of male and female cihateup ducks was equal  (50%:50%), however the sex ratio of alabio ducks was different (32%:68%). Mortality rate was affected by sex of duck (P<0.05). The Higher mortality was occured at early (day 0-7) and late (day>25) hatching period.